ASSESSMENT OF PTX3 LEVELS IN GINGIVAL CREVICULAR FLUID AND GINGIVAL INFLAMMATION DURING TOOTH ERUPTION IN CHILDREN WITH TYPE 1 DIABETES VERSUS CHILDREN WITHOUT SYSTEMIC CONDITIONS - Roxana Onea; Flavia Mirela Nicolae; Dora Maria Popescu; Marilena Bataiosu; Camelia Fiera Maglaviceanu; Claudiu Ionele; Carmen Niculescu; Mihail Virgil Boldeanu; Adina Turcu-Știolică; Allma Pitru (Romanian Journal of Oral Rehabilitation, 2023)
Background: The specialized literature has reported the presence of inflammatory periodontal changes among pediatric patients diagnosed with type 1 diabetes mellitus (T1DM). The aim of our study is to evaluate Pentraxin 3 (PTX3) levels in gingival crevicular fluid (GCF) of erupting teeth and gingival inflammation in children with and without T1DM. Methods: A total of 43 patients were included in this study, aged between 6-12 years, with 23 having a diagnosis of T1DM and 20 healthy patients. All subjects underwent periodontal examination, the values of the Silness-Loe Plaque Index (PI) and Gingival Index (GI) were recorded and GCF was collected from an erupting tooth. Results: Significant differences exist between the two groups regarding glycosylated hemoglobin (HbA1c), PTX3 levels, and GI values. In patients with T1DM, a strong significant correlation exists between PTX3 and HbA1c levels, as well as between PTX3 and PI and GI values. Additionally, a strong negative correlation was found between age and PI and GI values. There is also a strong positive correlation between HbA1c and PI and GI values. Conclusions: PTX3 levels in GCF and the gingival inflammation are significantly higher in children with diabetes during dental eruption, under conditions of comparable plaque accumulation.